Design of a Three-Layer Blockchain Integrity Validation Model for Fraud Prevention in Business Licensing Platforms - Edrian Hadinata; Tasya Febriyanti (Jurnal Armada Informatika, 2026)
Data integrity in multi-stage government licensing services is a critical challenge, particularly when each stage involves different actors with distinct authority. Without a permanent recording mechanism for every action in the workflow, licensing data remains vulnerable to manipulation. This study develops a web-based SIUP business licensing information system integrating blockchain technology as an automatic integrity validation mechanism. Every action taken by six actors is permanently recorded as a new block using SHA-256 hashing and Proof-of-Work requiring hash values prefixed with "00". The recording mechanism is implemented exclusively in BlockchainController.php through the validate() function, while block hash and prevHash values are stored in independent log files located at storage/app/private/blockchain/ on the server. A three-layer integrity validation runs automatically: the first layer compares block count in the database against the log file; the second layer verifies prevHash chain continuity; the third layer confirms that every block hash begins with "00" as proof of valid Proof-of-Work mining. When any violation is detected, the system disables all action buttons for every actor except the Head of Agency, who issues an official Blockchain Integrity Violation Certificate. Testing confirms that the three-layer mechanism successfully detects all violation scenarios automatically.